A Diachronic Study of the Practises of Translation of Gerunds and Gerundives from Latin into Old English and Middle English in History Narratives - Aarnio, Aki (My University, 2016)
This is a philologically oriented thesis which studies the possible adoption of a grammatical feature from one language into another from historical linguistic perspective. The foci of the study are, on the one hand, the Latin gerund and gerundive and, on the other hand, the English gerund. The material of this study consists of excerpts from two British history narratives in Latin and from the Old English and Middle English translations of these history narratives. The British history narratives selected for the material of this thesis are the 8th century Historia ecclesiastica gentis Anglorum by Bede and the 14th century Polychronicon by Ranulf Higden. Historia ecclesiastica gentis Anglorum has been compared with its Old English translation from the 11th century, the author of which is unknown. The Polychronicon, on the other hand, has been compared with two different Middle English translations: one from the 14th century, by John Trevisa; the other from the 15th century, the author of which is also unknown. The purpose of this thesis is to investigate whether the gerund, which was adopted into English by the Middle English period, has been used to translate the Latin gerunds and gerundives. At the basis of the study is the hypothesis that the English gerund has been used to translate the Latin gerunds and gerundives at least occasionally. The methodology of this thesis consists of detailed and qualitative study of the primary material. The primary material has been studied from synchronic, diachronic and paratextual perspective. The results of this thesis confirm that the English gerund has occasionally been used to translate the Latin gerunds and gerundives. The instances that confirm with the hypothesis are so rare, however, that the relationship between the English gerund and the Latin gerund and gerundive seems to be indirect or at least enshadowed by wide-ranging grammatical differences.